Developing Analog PWM Inverter for Induction Motor Control - Siti Nursyuhada, Mahsahirun; Ajisman, Apen (AENSI Publishing, 2014)
This switch-based power converter analog implementation is developed based on sinusoidal-PWM technique(SPWM). Center-aligned triangle is compared with 3-phase sinusoidal waves to produced SPWM signals; switching six (6) IGBTs SKM200GB123D for 3-phase induction motor inverter module. Op-amp, passive components and IR2130 bridge driver are used. The circuit is tested with slowly increased 80Vdc and manually adjustable carrier frequency capable to operate tested induction motor at rated speed. SPWM inverter has improves power efficiency of the induction motor.